2014
DOI: 10.1090/s0002-9947-2014-05956-4
|View full text |Cite
|
Sign up to set email alerts
|

A $B_p$ condition for the strong maximal function

Abstract: Abstract. A strong version of the Orlicz maximal operator is introduced and a natural Bp condition for the rectangle case is defined to characterize its boundedness. This fact let us to describe a sufficient condition for the two weight inequalities of the strong maximal function in terms of power and logarithmic bumps. Results for the multilinear version of this operator and for others multi(sub)linear maximal functions associated with bases of open sets are also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…The boundedness of those operators on L p spaces was thoroughly studied by C. Pérez [30], under the aditional condition that A is doubling, assumption that was proved to be superfluous by Liu and Luque [24]. The condition is the following…”
Section: 21mentioning
confidence: 99%
“…The boundedness of those operators on L p spaces was thoroughly studied by C. Pérez [30], under the aditional condition that A is doubling, assumption that was proved to be superfluous by Liu and Luque [24]. The condition is the following…”
Section: 21mentioning
confidence: 99%
“…Later on L. Liu and T. Luque [27], proved that imposing the doubling condition on A is superfluous. Now we compile some examples of maximal operators related to certain Young functions.…”
Section: Young Functions and Orlicz Spacesmentioning
confidence: 99%
“…Their covering lemma is quite useful by the reason that it overcomes the failure of the Besicovitch covering argument for rectangles with arbitrary eccentricities. The selection algorithm given by Córboda and Fefferman was used many times to gain end-point estimates for M R , as demonstrated in [5], [8], [11], [13], [21], [22], [23], [25]. The corresponding weighted version of (1.1) with w ∈ A 1,R was shown by Bagby and Kurtz [1].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, under more weaker condition (Tauberian condition) than v ∈ A ∞,B , Liu and Luque [21] investigated the strong boundedness of two-weighted inequality for the maximal operator M B . They showed that if M B satisfies the Tauberian condition (condition (A) [12], [16], [29]) with respect to some γ ∈ (0, 1) and a weight µ as follows: there exists a positive constant C B,γ,µ such that, for all measurable sets E, it holds that…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation